The shaping of a Christian family - Elliot, Elisabeth (Oliver Nelson, 1992)
Drawing from the Scriptures, her observations of family life in America over the past forty years, and her own upbringing, and offering a detailed description of the home in which she grew up, Elisabeth Elliot illustrates the foundational principles and values necessary to create a Christian home and family. More than a manual on raising children or a treatise on the biblical basics of family life, The Shaping of a Christian Family sheds light on the many facets of family living: homely joys and shared troubles, triumphs and tragedies, difficult choices and rich rewards. Readers who have not had the solid foundations of a strong and godly home will find here not only a pattern worth considering but fresh insights which answer the deep desires of the human heart. - Jacket flap.